“Environment Is Like Nature”: Opinions Of Children Attending Forest Kindergarten About The Concept Of Environment - AHİ, Berat; KAHRİMAN PAMUK, Deniz (International Electronic Journal of Environmental Education, 2021)
The purpose of the current study is to determine the opinions of children attending forest kindergarten about the concept of environment. The participants of the study are thirty six 50-70 month-old children attending a forest kindergarten. In line with the purpose of the study, the triangulation design, one of the qualitative research models, was used. In the quantitative dimension of the current study, the children were asked to draw what comes to their mind when they hear the word “environment” and then interviews were conducted with the children about their drawings. Then, on the basis of the codes derived from the drawings and DAET-R, it was attempted to understand the structure of their opinions about environment. In the qualitative dimension of the study, interviews were conducted according to the phenomenological design. As a result of the analyses conducted, it was concluded that the children generally evaluated nature as environment. In both drawings and interviews, the children generally drew and mentioned biotic and abiotic factors. The concepts of human and designed environment were rarely emphasized in the drawings and interviews. Given that the participating children were attending a forest kindergarten it was already expected by the researchers that their opinions would be “nature” centred. In light of these findings, it is thought that it is important to make educational programs built on environmental education more widespread.
Keywords: Environment and Culture; Çevre ve Kültür; child; concept of environment; forest school; nature; 13. Climate action; 4. Education; 16. Peace & justice